The role of student-teacher relationship to teacher subjective well-being as moderated by teaching experience - Irsyad Farhah; Airin Yustikarini Saleh; Shahnaz Safitri (Intelektual Pustaka Media Utama, 2021)
A good relationship between teachers and students can positively influence the subjective well-being of teachers. However, in the context of middle school setting, a good relationship with students was considered as an effortful attempt for teacher to maintain which was related to the teacher well-being too. It was said that the more teaching experience the teacher has, the easier for them to navigate their relationship with students. Therefore, this study aimed to test whether the teaching experience moderate the impact of the teacher-student relationship to the teacher subjective well-being. The teacher-student relationship was measured using the Student-Teacher Relationship Scale (STRS), while the teacher subjective well-being was measured by the Teacher Subjective Well-Being Questionnaire (TSWQ). Respondents in this study were 289 teachers at the middle school level from both junior high school and senior high school or equivalent. The analysis technique used was a simple moderation analysis. The result showed that there was a positive relationship between the teacher-student relationship, the teacher subjective well-being, and teacher experience. However, this study indicated that there was no moderation role of the teaching experience in weakening or strengthening the close teacher-student relationship impact on the teacher well-being.